The Pre-colonial Yoruba Education System: Catalyst Against Immorality - Layo Ogunlola (Yoruba Studies Review)
The notion that Africans in general have no literature of their own has been severally debunked as false assertion. Awólàlú (1979) describes it as ‘erroneous’, a thought borne out of prejudice, malice and bias (3). Among these is their method of training both the young and old in the ways and traditions of the people. The Yorùbá had a system of education referred to as ìlànà ètò è̩kó̩ ìbílè̩ (traditional or indigenous system of education). Even though the said system of education was not documented, it is not only flexible enough to conserve the tradition and culture of the people, it has also proved adequate in transmitting the cultural heritage from generation to generation using the mother-tongue as a tool. Tis paper examines the effectiveness of this traditional system of education in the development of the pre-colonial Yoruba society especially in terms of moral diligence. The paper critically analyzes the system and concludes that a society that is morally bankrupt cannot develop, hence the need for a system of education that emphasizes moral training such as the Yorùbá traditional system of education as compared with the Western system of education, which lays emphasis on jobs. The paper concludes that if the formal education system can prioritize moral training by tailoring the curriculum towards this objective, the problem of high moral decadence level currently ravaging our various societies may continue and this will not do the societies any good.